Polymorphism of Alcohol Metabolizing Gene ADH3 Predisposes to Development of Alcoholic Pancreatitis in North Indian Population - Singh, Divya; Negi, Tajwar S.; Upadhyay, Ghanshyam; Choudhuri, Gourdas (Frontiers in Molecular Biosciences, 2015)
Background and aim- Genetic factors regulating alcohol metabolism could predispose in developing alcoholic pancreatitis (ACP). Studies revealed that alcohol could be metabolized by both ways, oxidative and non-oxidative. The main oxidative pathway includes alcohol dehydrogenase (ADH), aldehyde dehydrogenase (ALDH) and cytochrome P450 enzyme. We investigated whether polymorphism in these alcohol metabolizing enzyme genes could be associated with alcoholic pancreatitis and is the purpose of our study. Method- Patients with alcoholic pancreatitis (ACP) (n=72), tropical calcific pancreatitis (TCP) (n=75), alcoholic controls (AC) (n=40) and healthy controls (HC) (n=100) were included in the study. Blood samples were collected from the subjects in EDTA coated vials. DNA was extracted and genotyping for ADH3, ALDH2 and CYP2E1 was done by PCR-RFLP (polymerase chain reaction- restriction fragment length polymorphism). The products were analyzed by gel electrophoresis. Result- The frequency distribution of ADH3*1/*1 genotype was significantly higher in ACP group (59.7%) compared with TCP (38.7%), HC (42%) and AC (37.5%) and was found to be associated with increased risk of alcoholic pancreatitis. There was no statistically significant difference between the frequency distribution of ADH3*1/*1, ADH3*1/*2 and ADH3*2/*2 genotype between TCP and HC and healthy alcoholics. ALDH2 gene was monomorphic in our population, and the frequencies for CYP2E1 intron 6 Dra I polymorphism were comparable in all four groups. Conclusion- This study shows that carriers of ADH3*1/*1 individuals consuming alcohol are at higher risk for alcoholic pancreatitis than those with other genotypes such as ADH3*1/*2 and ADH3*2/*2.